2014
DOI: 10.1037/a0037047
|View full text |Cite
|
Sign up to set email alerts
|

How arousal modulates the visual contrast sensitivity function.

Abstract: Recent evidence indicates that emotion enhances contrast thresholds in subsequent visual perception (Phelps, Ling, & Carrasco, 2006), and perceptual sensitivity for low-spatial-frequency but not high-spatial-frequency targets (Bocanegra & Zeelenberg, 2009b). However, these studies just report responses to various frequencies at a fixed contrast level or responses to various contrasts at a fixed frequency. In the current study, we measured the full contrast sensitivity function as a function of emotional arousa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 61 publications
5
53
2
1
Order By: Relevance
“…It is possible that this higher arousal facilitated participants' responses to the angry faces, which also had a higher level of arousal. Studies have shown that presenting an arousing cue (e.g., a fearful face or a fear-conditioned auditory tone) enhances contrast sensitivity in subsequent visual perception (Lee et al 2014;Phelps et al 2006). Moreover, arousing and nonarousing visual stimuli themselves can differ in low-level visual features, such as the energy distribution of frequencies (e.g., Delplanque et al 2007).…”
Section: Discussionmentioning
confidence: 98%
“…It is possible that this higher arousal facilitated participants' responses to the angry faces, which also had a higher level of arousal. Studies have shown that presenting an arousing cue (e.g., a fearful face or a fear-conditioned auditory tone) enhances contrast sensitivity in subsequent visual perception (Lee et al 2014;Phelps et al 2006). Moreover, arousing and nonarousing visual stimuli themselves can differ in low-level visual features, such as the energy distribution of frequencies (e.g., Delplanque et al 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have demonstrated that changes in emotional states are associated with changes in perceptual or cognitive processes, including visual perception (Gasper, 2004; Phelps et al, 2006; Bocanegra and Zeelenberg, 2009; Kuhbandner et al, 2009; Lee et al, 2014a), temporal attention (Jefferies et al, 2008), spatial attention (Phelps et al, 2006), and cognitive control (van Wouwe et al, 2009; van Steenbergen et al, 2010; Kuhbandner and Zehetleitner, 2011). Influences of mood on basic auditory processing, however, have remained largely unexplored [see Siegel and Stefanucci (2011) for a recent exception].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, following previous studies that demonstrated effects of emotion cues on contrast sensitivity in the visual domain (Phelps et al, 2006; Bocanegra and Zeelenberg, 2009; Lee et al, 2014a), we used a perceptual performance measure rather than brain indices of auditory processing. To the best of our knowledge only one other recent study has investigated how mood impacts basic auditory perception (Siegel and Stefanucci, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Once an emotional stimulus is presented, it changes the way subsequently presented neutral objects compete for attention. For example, the ability to detect a solitary neutral stimulus can be enhanced by presenting an emotionally arousing stimulus just beforehand (Bocanegra & Zeelenberg, 2009; Padmala & Pessoa, 2008; Zeelenberg & Bocanegra, 2010), at least if the stimulus has low spatial frequency (Lee, Baek, Lu, & Mather, in press). Moreover, the presentation of an emotional stimulus has also been shown to enhance the ability to identify a neutral target within an array of neutral distracters (Becker, 2009; Olatunji, Ciesielski, Armstrong, & Zald, 2011; Phelps, Ling, & Carrasco, 2006).…”
Section: Introductionmentioning
confidence: 99%